Análisis de diseño para el desarrollo de un CRM en el Crossfit Puertas Negras CF en la ciudad de Babahoyo. - Echeverria Vallejo, Mayerly Scarlet (2024)
This case study focuses on the design and implementation of a customer relationship management (CRM) system for the CrossFit Puertas Negras CF gym in Babahoyo. The main objective is to develop a CRM that improves the administration of the gym, optimizing the management of reservations, communication between trainers and members and monitoring the progress of users. To achieve this, surveys were conducted with 2 trainers and 200 members in three different shifts: morning, afternoon and evening. Analysis of the surveys revealed some specific user needs of both gym members and coaches who expressed a strong preference for a user interface that is easy to navigate and which would improve communication within the system as well as some internal messaging and functionality. The study underscored the importance of including advanced features to facilitate communication and allow for individual progress detailing that will not only improve the user experience but also provide more personalized and effective tracking.